2006
DOI: 10.1128/aem.72.4.2306-2312.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epsilon-Poly- l -Lysine Biosynthesis in Streptomycetaceae Bacteria by Short-Chain Polyols

Abstract: Antimicrobial epsilon-poly-L-lysine (ePL) is secreted by Streptomycetaceae bacteria, and the mechanism of ePL biosynthesis remains to be elucidated. We previously reported that an unknown ePL derivative accumulates in the culture medium of ePL-producing bacteria when glycerol is added to the culture medium (Nishikawa and Ogawa, Appl. Environ. Microbiol. 68: [3575][3576][3577][3578][3579][3580][3581] 2002). In this study, by using matrix-assisted laser desorption ionization-time of flight mass spectrometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Thus, mutating the linker regions connecting the TM domains should be a good strategy for effective production of short-chain ε-PL. In addition to this strategy, it is known that the use of ε-PL production media containing polyols such as glycerol, ethylene glycol, and trimethylene glycol resulted in the shortening of the ε-PL chain length (6,26); the S. albulus NBRC14147 strain produced a short-chain ε-PL (13-to 28-mer) in the ε-PL production medium containing 2.5% pentamethylene glycol (1,5-pentanediol). However, the polymer was produced as an ester formed between the terminal carboxyl group of ε-PL and a hydroxyl group of pentamethylene glycol.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mutating the linker regions connecting the TM domains should be a good strategy for effective production of short-chain ε-PL. In addition to this strategy, it is known that the use of ε-PL production media containing polyols such as glycerol, ethylene glycol, and trimethylene glycol resulted in the shortening of the ε-PL chain length (6,26); the S. albulus NBRC14147 strain produced a short-chain ε-PL (13-to 28-mer) in the ε-PL production medium containing 2.5% pentamethylene glycol (1,5-pentanediol). However, the polymer was produced as an ester formed between the terminal carboxyl group of ε-PL and a hydroxyl group of pentamethylene glycol.…”
Section: Discussionmentioning
confidence: 99%
“…A feature which makes this hydrogel unique is the incorporation of two naturally occurring components; pεK is an edible, non-toxic material currently used as an emulsifi er and preservative in foodstuffs and classifi ed as "generally regarded as safe" (GRAS) by the US Food and Drug Administration since 2004. [16][17][18] Short chain bis-carboxy fatty acids are found in both plants and animals. In the latter they are products of the oxidative degradation of longer chain fatty acids.…”
Section: Doi: 101002/adhm201600258mentioning
confidence: 99%
“…Additional short-chain polyols or modified cyclodextrins in the culture broth were also observed to regulate the chain length of ɛ-PL. Nishikawa and Ogawa found that ɛ-PL elongation was inhibited by the polyols via esterification; the ɛ-PL esters were formed during L-lysine polymerization, and the number of L-lysine residues of ɛ-PL-polyol esters decreased with increasing polyol concentration (Nishikawa and Ogawa 2006). Thus, it is feasible to control the number of Llysine residues in ɛ-PL by regulating the polyol concentration in the culture broth.…”
Section: Molecular Weight Of Microbial ɛ-Plmentioning
confidence: 95%
“…In 2002, a high-efficiency method was developed to screen ɛ-PL-producing strains by detecting the color zone formed by the secreted ɛ-PL (Nishikawa and Ogawa 2002). Since then, more and more studies have been performed to exploit the microbial ɛ-PL, including screening of new ɛ-PL-producing strains, development of new fermentation processes, control of the molecular weight of ɛ-PL, and discovery of ɛ-PL degrading enzymes and synthetase (Hamano et al 2006;Hirohara et al 2006Hirohara et al , 2007Nishikawa 2009;Nishikawa and Ogawa 2006;Shih and Shen 2006a, b;Shih et al 2006;Yamanaka et al 2008). In recent years, with the development of genetic engineering, bioinformatics, and advanced precision instruments and testing equipment, the biosynthetic mechanism of microbial ɛ-PL has been investigated more and more.…”
Section: Introductionmentioning
confidence: 99%